Efektivitas Ekstrak Daun Komak (Lablab purpureus) Terhadap Sistem Imun Ikan Nila (Oreochromis niloticus) Yang Diinjeksi Bakteri Aeromonas hydrophila - Rabi’atussamiah; Azhar, Fariq; Abidin, Zaenal; setyowati, Dewi Nur’aeni (Jurnal Media Akuakultur Indonesia, 2024)
This study aims to determine the effect of comma leaf extract on the immune system of tilapia injected with A. hydrophila bacteria. This research was conducted for 60 days at the Fish Production and Reproduction Laboratory and Aquaculture Fish Health Laboratory, Aquaculture Study Program, Department of Fisheries and Marine Sciences, Faculty of Agriculture, University of Mataram. The method used was a completely randomized design (CRD) experiment with five treatments and three replications, namely where K- was not given comma leaf extract and was injected with 0.9% NaCl, K+ was not given comma leaf extract and was injected with A. Hydrophila bacteria, P1 (0.5%) extract comma leaf and injected with A. hydrophila bacteria, P2 (1%) of komak leaf extract and injected with A. hydophila bacteria, P3 (2%) of komak leaf extract and injected with A. hydrophila bacteria. The observed parameters were total erythrocytes, total leukocytes, hemoglobin, hematocrit, differential leukocytes, phagocytosis activity, total bacteria and survival (SR). The results showed that the average value of total erythrocytes was 1.22-1.82 x106 cells/mm3, total leukocytes were 2.08-2.8 x104 cells/mm3, hemoglobin was 3.4-5.5%, hematocrit was 14.1-17.3%, differential leukocytes consisted of 4 types of cells, namely lymphocytes. , monocytes, neutrophils and platelets. Lymphocytes 60.7-72.3%, monocytes 4.3-7.3%, neutrophils 17-24.3%, and platelets 6.3-7.7%, phagocytosis activity 44.8-66.3%, total bacteria (TB) OD620 3.39-3.84, survival (SR) 46.7-66.7 %. The addition of 2% of comma leaf extract to the feed can improve the immune system of tilapia injected with A. hydrophila bacteria